Partnering for impact: Integrated transmission assessment surveys for lymphatic filariasis, soil transmitted helminths and malaria in Haiti. - Alaine Kathryn Knipes; Jean Frantz Lemoine; Franck Monestime; Carl R Fayette; Abdel N Direny; Luccene Desir; Valery E Beau de Rochars; Thomas G Streit; Kristen Renneker; Brian K Chu; Michelle A Chang; Kimberly E Mace; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:Since 2001, Haiti's National Program for the Elimination of Lymphatic Filariasis (NPELF) has worked to reduce the transmission of lymphatic filariasis (LF) through annual mass drug administration (MDA) with diethylcarbamazine and albendazole. The NPELF reached full national coverage with MDA for LF in 2012, and by 2014, a total of 14 evaluation units (48 communes) had met WHO eligibility criteria to conduct LF transmission assessment surveys (TAS) to determine whether prevalence had been reduced to below a threshold, such that transmission is assumed to be no longer sustainable. Haiti is also endemic for malaria and many communities suffer a high burden of soil transmitted helminths (STH). Heeding the call from WHO for integration of neglected tropical diseases (NTD) activities, Haiti's NPELF worked with the national malaria control program (NMCP) and with partners to develop an integrated TAS (LF-STH-malaria) to include assessments for malaria and STH. METHODOLOGY/PRINCIPLE FINDINGS:The aim of this study was to evaluate the feasibility of using TAS surveys for LF as a platform to collect information about STH and malaria. Between November 2014 and June 2015, TAS were conducted in 14 evaluation units (EUs) including 1 TAS (LF-only), 1 TAS-STH-malaria, and 12 TAS-malaria, with a total of 16,655 children tested for LF, 14,795 tested for malaria, and 298 tested for STH. In all, 12 of the 14 EUs passed the LF TAS, allowing the program to stop MDA for LF in 44 communes. The EU where children were also tested for STH will require annual school-based treatment with albendazole to maintain reduced STH levels. Finally, only 12 of 14,795 children tested positive for malaria by RDT in 38 communes. CONCLUSIONS/SIGNIFICANCE:Haiti's 2014-2015 Integrated TAS surveys provide evidence of the feasibility of using the LF TAS as a platform for integration of assessments for STH and or malaria.